(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
A 27 years old male presented with Class-II div 1 malocclusion with a mesodense. Treatment involved extraction of mesiodense. The alignment of teeth of both arch was achieved by edgewise orthodontic therapy. Ban J Orthod & Dentofac Orthop, April 2015; Vol-5 (1-2), P.27-29